Edukasi Pengetahuan Menjaga Kesehatan Mata Siswa SDN 004 Samarinda Ilir - Cahyaningrum, Gyta; Naheria, Naheria; Hamdiana, Hamdiana; Cahyono, Didik; Fauzi, Muhammad Sukron (Lembaga Dongan Dosen, 2024)
The eye health knowledge education program is one form of program to increase students' awareness and understanding of how to maintain eye health, prevent visual impairment, and improve quality of life. The method of this community service activity is a qualitative approach, which is carried out at SDN 004 Samarinda Ilir, the participants in this activity include students and teachers. Data collection uses observation techniques as preparation, implementation of education and training, and evaluation. After the implementation of the educational program, students can know and understand the habits that need to be avoided and limited in terms of gadget use, and students can explain the impact and risks of excessive gadget use. The results of the educational program to maintain eye health that was implemented showed a difference in the level of understanding and knowledge of students before education obtained a percentage of 35% and after education, the percentage increased to 82%. This difference shows that the educational intervention provided has a positive impact on student understanding so it shows a significant increase in the level of experience and knowledge of students regarding eye health.